The Potential Use of the FBC Ash for the Preparation of Blended Cements - Gazdič, Dominik; Fridrichová, Marcela; Kulísek, Karel; Vehovská, Ludmila (Procedia engineering, 2017)
Ashes from fluidized bed combustion, i.e. FBC ashes, are not being practically used for the production of hydraulic binders. The problem is their chemical and mineralogical composition. FBC ashes are characterized by a higher content of SO3, highly active free CaO and sometimes higher loss on ignition. The higher proportion of these substances has resulted in volume and temperature instability. However, FBC ashes could be used within a certain limit concentration in binders with relatively similar chemical-mineralogical composition such as Portland cement. The potential use of FBC ash for the preparation of blended Portland cements was studied in this paper. For this purpose, two types of FBC ashes and one type of traditional fly ash were selected. The first representative was a filter FBC ash, the second one was a bed FBC ash. Fly ash from pulverized coal combustion was used for comparison. The samples were prepared by co-grinding of the selected ash, Portland clinker and gypsum in a laboratory ball mill to a given value of specific surface area. Ash content was 15% and 30% of the total sample weight. The samples were subjected to the determination of basic technological properties – the water/cement ratio, setting times, strength, and soundness. The course of the hydration process was monitored by the qualitative method of X-ray diffraction analysis (XRD). The hydration product quantification was performed by the thermogravimetric analysis (TGA/DTA). The amount of CaO attributable to Ca(OH)2 and CaCO3 was quantified. Based on the results, a conclusion was made that the utilization of FBC ash in blended Portland cement production is possible. The values of the physical-mechanical properties of the blended cements based on FBC ashes are similar to the reference. In the case of lower FBC ash content, they are even comparable with ordinary Portland cement.